An Observational Study: Association Between Atopic Dermatitis and Bacterial Colony of the Skin Based on 16S rRNA Gene Sequencing - Yang XP; Liu YY; Zhang CY; Huang KK; Han SS; Liang BY; Lin Y (Dove Medical Press, 2024)
Xian-Ping Yang,1,* Ying-Yao Liu,2,* Cai-Yun Zhang,3 Kai-Kai Huang,1 Shan-Shan Han,1 Bao-Ying Liang,1 Ying Lin1 1Department of Dermatology, the Second Affiliated Hospital of Guangzhou University of Chinese Medicine (Guangdong Provincial Hospital of Chinese Medicine), Guangzhou, Guangdong, People's Republic of China; 2The Second Clinical Medical College, Guangzhou University of Chinese Medicine, Guangzhou, Guangdong, People's Republic of China; 3Department of Dermatology, Dongguan Traditional Chinese Medicine Hospital, Dongguan, Guangdong, People's Republic of China*These authors contributed equally to this workCorrespondence: Ying Lin, Department of Dermatology, the Second Affiliated Hospital of Guangzhou University of Chinese Medicine (Guangdong Provincial Hospital of Chinese Medicine), No. 111 Dade Road, Guangzhou, Guangdong, 510120, People's Republic of China, Email lin19791226@gzucm.edu.cnAim: Atopic dermatitis (AD) often accompanies skin infections, and bacterial skin infections often cause persistent and worsening symptoms. In this study, we explored the key changes in the microbiota of AD patients, as well as the effects of different ages and the severity of rash on changes in the microbiota.Patients and Methods: A total of 95 AD patients and 77 healthy volunteers were recruited. The AD patients were divided into three groups based age and three groups according to the EASI score. Microorganisms collected from the skin were analyzed through 16S rRNA gene sequencing, revealing species diversity via α and β diversity analyses. Species compositions were compared at the phylum and genus levels. The significance of skin microbiota at the genus level was assessed using the random forest algorithm. Finally, the impact of relationships between different microbial communities on the microbial community composition and the pathogenesis of AD was explored using Pearson correlation coefficients.Results: The species diversity of the skin microbiota in the AD group significantly decreased. Compared with that in the healthy volunteers (HV) group, the bacterial diversity in the two groups of samples significantly differed. Staphylococcus dominated the bacterial communities, and as AD symptoms gradually worsened, the abundance of Staphylococcus gradually increased. Among all bacterial genera with a relative abundance greater than 1%, Staphylococcus showed a negative correlation with other genera, and showed significant consistency in specimens from different age groups.Conclusion: Changes in the abundance of Staphylococcus in the skin bacterial colonies are the main cause of AD. Brevundimonas, Paracoccus, Corynebacterium, and Veillonella may serve as characteristic biomarkers for AD. These results indicate that altering the microbiota composition of the skin may aid in the treatment of AD.Keywords: atopic dermatitis, skin bacterial colony, 16S rRNA gene sequencing